Implementasi Akad Murabahah Pada BMT Usaha Mulya Masjid Raya Pondok Indah Jakarta - Tiara Kirana Prameswari; Daffa Putra Alvaro; Erlinda Sheila Amanda; Falikhatun Falikhatun (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to identify the application of sharia principles that are applied to the BMT Masjid Raya Pondok Indah Jakarta. Nowadays, the problems that develop in the community regarding murabahah contracts, especially those carried out by the BMT, are deviating from sharia principles. This study uses an exploratory research method, namely by using the interview method to obtain data from the BMT of the Pondok Indah Syariah Raya Mosque, Jakarta. The results of this study indicate that in practice, BMT has implemented a murabahah contract in accordance with sharia principles. However, BMT Masjid Raya Pondok Indah Jakarta Sharia encountered obstacles in applying for other funding sources, due to many doubts and difficulties in practice.